1992
DOI: 10.1111/j.1467-6486.1992.tb00689.x
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Corporate Performance From Organizational Culture*

Abstract: This article investigates the relationships of culture strength and two substantive cultural values with corporate performance. Culture strength is measured by the consistency of responses to survey items across people and the two cultural values are measured by items on the survey that relate to either adaptability or stability. The data, from management surveys of 11 US insurance companies in 1981, were correlated with asset and premium grow,th rates from 1982 to 1987. Results indicate that both a strong cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
333
1
21

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 594 publications
(396 citation statements)
references
References 28 publications
15
333
1
21
Order By: Relevance
“…The organizational culture types also demonstrated strong correlations with transformational leadership traits as it relates to team builders, facilitators, nurturers, mentors, and supporters. This study also found organizational effectiveness to be positively correlated with transformational leadership, hierarchy and clan culture which is consistent with the research conducted by Gordon & DiTomaso (2003) that also found transformational leadership to be positively correlated with satisfaction and leader's effectiveness. Further research is also required to investigate a wider sampling frame and to examine the relationship between leadership and culture behaviors and their relevant organizational outcomes.…”
Section: Conclusion and Policy Implicationssupporting
confidence: 80%
“…The organizational culture types also demonstrated strong correlations with transformational leadership traits as it relates to team builders, facilitators, nurturers, mentors, and supporters. This study also found organizational effectiveness to be positively correlated with transformational leadership, hierarchy and clan culture which is consistent with the research conducted by Gordon & DiTomaso (2003) that also found transformational leadership to be positively correlated with satisfaction and leader's effectiveness. Further research is also required to investigate a wider sampling frame and to examine the relationship between leadership and culture behaviors and their relevant organizational outcomes.…”
Section: Conclusion and Policy Implicationssupporting
confidence: 80%
“…and DiTomasso, 1992). The second is the contentious view that work culture is subject to conscious manipulation by management, who are argued to be capable of directing culture to their desired end (Deal and Kennedy, 1982;Pascale and Athos, 1981;Peters and Waterman, 1982).…”
Section: Topicalmentioning
confidence: 99%
“…The most studied hypothesis by the literature is that broadly established cultures strengthen organizational performance. In support to this argument, some empirical studies show that companies with well established cultures achieve higher performance than those characterised by weak cultures (Kotter and Heskett, 1992;Gordon and Di Tomaso, 1992). Indeed, Kotter and Heskett (1992) reveal that during a 10-year period, companies that deliberately designed their cultures, obtained higher performance than those that did not have a well developed culture.…”
Section: Organizational Culture and Performancementioning
confidence: 72%
“…This author suggests that companies with strong cultures are extremely good at taking advantage of established competences, but they find difficulties in order to discover new competences that best fit with the changing environment conditions. These results suggest that the best strategy for companies would be to develop cultures clearly based on an exploratory learning attitude and innovation (Gordon and Di Tomaso, 1992).…”
Section: Organizational Culture and Performancementioning
confidence: 99%